Risk stratification and prognostic factors in patients with pulmonary arterial hypertension and comorbidities a cross-sectional cohort study with survival follow-up - Xanthouli, Panagiota; Kögler, Maria; Marra, Alberto M.; Benjamin, Nicola; Fischer, Lukas; Eichstaedt, Christina; Harutyunova, Satenik; Nagel, Christian; Grünig, Ekkehard; Egenlauf, Benjamin (Respiratory research, 2020)
The objective of this study was to analyze prognostic factors and risk stratification in patients with pulmonary arterial hypertension (PAH) and comorbidities.
Gesehen am 23.03.2021